2011
DOI: 10.1097/01.aoa.0000406674.79164.31
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Decreases the Failed Labor Epidural Rate in Resident Trainees

Abstract: A lthough epidural analgesia is used widely for pain relief during labor, the failure rate ranges from 1.5% to 20%. This prospective, randomized, nonblinded study investigated whether ultrasound measurement of the depth from the skin to the epidural space before epidural placement decreases the failure rate of labor analgesia. The second objective of the study was to correlate the ultrasoundmeasured depth to the epidural space with the actual depth of the needle when the epidural space is reached.A total of 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 0 publications
2
81
0
1
Order By: Relevance
“…Several clinical studies have reported that neuraxial pre-procedural imaging decreases the number of attempts required for epidural placement, determines the optimal puncture site and needle angulation, and accurately predicts the depth from the skin to the epidural space (2,5). Superior epidural catheter function and fewer replacement rates are other reported benefits of ultrasoundguided epidural placement (Table 2) (2, 5).…”
Section: Pre-procedural Neuraxial Ultrasound Versus Standard Blind Tementioning
confidence: 99%
See 4 more Smart Citations
“…Several clinical studies have reported that neuraxial pre-procedural imaging decreases the number of attempts required for epidural placement, determines the optimal puncture site and needle angulation, and accurately predicts the depth from the skin to the epidural space (2,5). Superior epidural catheter function and fewer replacement rates are other reported benefits of ultrasoundguided epidural placement (Table 2) (2, 5).…”
Section: Pre-procedural Neuraxial Ultrasound Versus Standard Blind Tementioning
confidence: 99%
“…It has been shown to improve the epidural placement learning curve by increasing the epidural success rate, and reducing the number of epidural attempts and catheter replacement for failed labor analgesia (4,5,8).…”
Section: Pre-procedural Neuraxial Ultrasound Versus Standard Blind Tementioning
confidence: 99%
See 3 more Smart Citations